The Representation of Women in USA Sports, Sports Administrative, and Team Sports Leadership - Aly, Ezzeldin R; Breese, Kathryn (European Scientific Journal, ESJ, 2018)
Woods (2016, p. 311) stated “For centuries, sports participated in assigning a limited role to women by excluding them from participation and resisting efforts to include them.” Women have had to struggle when it comes to sport leadership positions. Women are not usually found in higher level jobs in sport, but they tend to have positions in lower management or lower profile positions. This study is a compilation of research into how people within collegiate athletics in the United States feel about women’s employment status in the field. A pilot interview was created and administered to three women: an athletic director, an athlete, and a professor at Florida A &M University. A surveywas created and administered to 30 subjects that have careers in sport leadership positions. The questions were divided into five categories consisting of representation, coaching, equal pay, and team sports. The survey showed that there are mixed feelings in the profession. Two-thirds of the subjects thought that there was a lack of female leadership within team sports. A little over half of the subjects thought that men were more successful in the areas of leadership, coaching, equal pay, representation, and team sports. By identifying the issues that women are facing when heading into this profession, the researchers identified what actions need to take place in order to resolve the problems discovered. In turn, this would create more opportunities and more qualified female candidates for positions in sports administration and team sports leadership in the United States.